Towards Nutrient Cycling in an Integrated Cattle-Cassava Fodder Farming System - Che, Minh Tung (2001)
An initial investigation was undertaken at two commercial cattle farms (Kuang and Banting) prior to the actual experimentation of this thesis to elucidate the potential of environmental pollution from the unprocessed slurries of semiintensive cattle production units, which were washed into the nearby waterways. The biological oxygen demand (BOD) and chemical oxygen demand (COD) of wastewater from the above farms were 5,560 and 19,492 mg/L and 4,703 and 13,280 mg/L, respectively. These values are well above the national permissible standards of 50 mg/L BOD and 100 mg/L COD for wastewater discharged from livestock farms. Based on the above findings, experiments were conducted with the aim to reduce the impact of cattle manure on the environment. The first experiment was conducted to identify local cassava varieties, namely MM 92 (MM), Black Twig (BT) and Medan (MD) which were of high yielding and capable of extracting large quantities of nutrients from the soil fertilized with livestock manure. DIy fodder yields ofMM, BT and MD over the 8 harvests amounted to 8.6, 8.0 and 6.2 t/ha, respectively. They produced 2.2, 1.9 and 1.5 t/ha of crude protein (CP), respectively. The plant mortality rates were 9.9, 14.0 and 14.0% for MM, BT and MD, respectively. The results suggest that agronomically, MM is the most suitable variety. The second experiment consisting of two trials was conducted to compare the ruminal and intestinal disappearances of cassava fodder (CaF) and grain concentrates (GC) in cattle. Three Charolais-Kedab Kelantan heifers weighing 300 kg, and each fitted permanently with ruminal and duodenal cannulae were used. The cattle were given a basal diet consisting of 70% oil palm frond (OPF), 15% GC and 15% CaF at 1.5% DM (dry matter) of their body weight. The DM effective degradability of CaF and GC was similar at the outflow whilst the CP effective degradability of CaF was higher than that of GC. Cassava fodder containing more than 20% CP was a good protein supplement for ruminants. Both CaF and GC could serve as a source of readily available N for synthesis of rumen microbial protein. Intestinal DM and CP disappearances of GC were much higher than those of CaF, implying that GC provided a higher proportion of digestible bypass nutrients than CaF.